Effective mechanical reinforcement of inorganic polymers using glass fibre waste. (10th November 2017) - Novais, Rui M.; Carvalheiras, J.; Seabra, M.P.; Pullar, R.C.; Labrincha, J.A.
Abstract: Glass fibre waste (GFW) coming from wind turbine blade production was used for the first time as a reinforcement agent in inorganic polymer (geopolymer) production. The influence of glass fibre content and length on the inorganic polymer microstructure, apparent density, and compressive and tensile strength was evaluated. Results demonstrate that the use of short, randomly distributed fibres significantly enhance the geopolymers' compressive strength (by up to ∼162%) and tensile strength (by up to ∼77%), while overcoming the brittle nature of the geopolymers. It was also found that the glass fibre content, rather than the fibre length, is the dominant factor affecting the geopolymers' mechanical properties. These results demonstrate the possibility of using an unexplored waste stream (glass fibre waste) as a reinforcement agent in inorganic polymers, which may reduce the amount of wastes in landfill and lower inorganic polymer production costs, while simultaneously contributing towards the circular economy. Graphical abstract: Image Highlights: Glass fibre waste coming from wind turbine blade production was reused. This unexplored waste was used as reinforcement agent in inorganic polymers. The fibres significantly increase geopolymers' compressive strength (up to 162%). Fibres incorporation enhanced tensile strength (∼77%) and geopolymers' ductility. This innovative solution contributes towards the circular economy.